He–Ne–Ar isotopic constraints on the mantle source of the Fani Maoré paroxysm: implications for plume involvement beneath the Comoros - Romain Sauvalle; Manuel Moreira; Bruno Scaillet; Nathalie Feuillet; Camille Gasser; Stephan J. Jorry (Earth and Planetary Science Letters, 2026)

Extreme Mediterranean rainfall impact on sedimentary routing systems: what can we learn from Storm Alex using in situ detrital 10Be? - Apolline Mariotti; Pierre-Henri Blard; Julien Charreau; Samuel Toucanne; Stephan Jorry; Olivier Joseph (Geomorphology, 2026)

Late Holocene and recent cold-water coral calcium carbonate production in Guilvinec Canyon, Bay of Biscay, France - Evan Edinger; Jean-François Bourillet; Lenaïck Menot; Franck Lartaud; Mathilde Chemel; Stephan Jorry (Deep Sea Research Part II: Topical Studies in Oceanography, 2025)

Decadal timescale evolution of coral islands: insights from Lakshadweep Archipelago - Shradha Menon; Pankaj Khanna; Saikat Kumar Misra; Stephan J. Jorry (Frontiers in Marine Science, 2024)
Low–lying coral islands are susceptible to rising sea levels and climate change, posing risks to island habitability over the next century. The decadal timescale evolution of the islands can provide an understanding of the governing controls of change and island response. This study investigates variations in the shoreline morphology of the Lakshadweep coral islands (Northern Indian Ocean/Arabian Sea) using satellite datasets (2003–2022; CNES/Airbus;0.3m – 0.7m resolution) and sedimentological data. Of the thirty islands (ten inhabited), six islands (Bangaram, Thinnakara, Suheli, Minicoy, Androth and Bitra) have been studied. Most of these islands are less than 1 km 2 in size except Androth and Minicoy (>4 km 2 ). While the data is discontinuous for the islands due to cloud obscuring, the shoreline morphology depicts variations for all the islands’ studied, irrespective of habitation and size. Larger islands have undergone consistent erosion since 2007 (total land loss is approximately 3 - 5% cumulatively). Smaller islands have undergone lateral migration, with sediment erosion usually along the southern edge and sediment migration and accumulation northwards, however, overall, their size remains consistently stable. The migration of sediments is observed only from 2007–2017, which coincides with severe El–Nino Southern Oscillation (ENSO) and low amplitude positive Indian Ocean Dipole (IOD) events. Furthermore, sedimentological analysis along Bangaram’s (small island) accreting margin reveals unconsolidated bio-detrital grainstones with predominant sand-sized fractions (2 – 0.25mm). Corals (43%), molluscs (33%), forams (13%), and algae (8%) are the major sediment producers (with 3% unidentified bioclasts). The ongoing climate warming and ocean acidification will influence the carbonate sediment budget in addition to the changing hydrodynamics owing to monsoons, cyclones, and coupled ocean-atmospheric regional phenomenon, altering the sediment production, transport and accumulation on these islands. Furthermore, rising sea levels and consequent erosion by wave action might lead to rapid drowning in the next few centuries. Our study identifies the current status of the island size variability in the Lakshadweep Archipelago and how site-specific and global factors influence them, thus providing insights into assessing the habitability within these low-lying coral islands.

Mantle xenolith-bearing phonolites and basanites feed the active volcanic ridge of Mayotte (Comoros archipelago, SW Indian Ocean) - Carole Berthod; Etienne Médard; Andrea Di Muro; Théo Hassen Ali; Lucia Gurioli; Catherine Chauvel; Jean-Christophe Komorowski; Patrick Bachèlery; Aline Peltier; Mhammed Benbakkar; Jean-Luc Devidal; Pascale Besson; et al. (Contributions to Mineralogy and Petrology, 2021)

Sedimentology and distribution of late quaternary calciturbidites and calcidebrites in the Mozambique Channel (Southwest Indian Ocean) - John W. Counts; Stephan J. Jorry; Natalia Vazquez-Riveiros; Lawrence A. Amy; Ewen Dennielou; Gwenael Jouet (Facies, 2021)